DAMPAK PENGETAHUAN TERHADAP KECEMASAN DALAM MENGHADAPI MENARCHE PADA REMAJA PUTRI DI SMP NEGERI 12 MAKASSAR - Rosmiati Ros Rosmiati; Sri Wahyuni Jindar (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Menarche (first menstruation) is the first menstruation that occurs in the uterine wall and is known as menstrual blood, the first menstruation is a sign of biological readiness, and a sign of the fertile cycle has begun. The readiness to face menarche is a condition that showing a readiness of someone to achieve the physical maturity which is a coming of menarche; this is characterized by an understanding of knowledge about the menstrual process so that they are ready to accept and experience menarche as a normal process. Teenagers' ignorance of menstruation can make it difficult to accept menarche. The purpose of this study was to determine the relationship of knowledge with the anxiety of young women facing menarche. This study, used was non-experimental research with analytic survey methods using a cross sectional approach. Sampling using a purposive sampling technique, found 66 respondents in accordance with the inclusion criteria. Data collection was carried out using a questionnaire and tested using a chi square statistical test where α = 0.002 with the help of statistical package for social science (SPSS) The results of bivariate analysis found that there is a relationship of knowledge about menarche with the anxiety of facing menarche grade VII students at SMP Negeri 12 Makassar. With ρ is 0.002 while the value α = 0.05. So it can be concluded